Child Migrants in Family Detention in the US: Addressing Fragmented Care - Shela Sridhar; Vasileia Digidiki; Leah Ratner; Dennis Kunichoff; Matthew G. Gartland (MDPI AG, 2024)
Background/Objectives: Migrant children in family detention facilities often experience frequent relocations and prolonged stays in precarious living conditions. This frequent relocation results in fragmentation of necessary medical care, leading to delays and inadequate medical care. We aim to highlight the critical need for comprehensive medical documentation in immigration detention facilities, a fragmented health care system and potential harm to these children without appropriate medical documentation. Methods: We conducted a retrospective review of 165 medical records from children detained at the Karnes County Family Residential Center between June 2018 and October 2020 to evaluate the adequacy of pediatric medical documentation in an Immigration and Customs Enforcement (ICE) family detention facility. Specific areas of interest included acute care, nutrition, immunization, developmental screening, and tuberculosis screening. Simple descriptive statistics were used to analyze the data. Results: Only 25% of 418 acute medical care visits included specific diagnoses. There was no documentation regarding follow-up recommendations upon release. 97% of children had a chest X-ray completed for tuberculosis screening, however no follow-up recommendations were documented for those with granulomas. Vaccination histories were inconsistently documented. No nutritional categorizations were completed despite 16% of children being at risk for malnutrition or already malnourished. Conclusions: Our findings revealed significant gaps in documentation, particularly in medical decision-making and clinical reasoning. In a fragmented medical system, inadequate documentation can result in avoidable errors in diagnosis and management. Improving documentation practices is crucial to ensure that all children, regardless of immigration status, receive quality healthcare aligned with national and international standards.